Enhanced biofilm-dependent biogas upgrading from waste activated sludge fermentation liquor in microbial electrolysis cells - Li, Lei (2025)
This study demonstrated that metal-organic frameworks (MOFs)-derived Fe-NC cathode improved both methane yield and methane content in a microbial electrolysis cell-coupled anaerobic digestion (MEC-AD) system treating waste activated sludge (WAS) fermentation liquor. Results revealed that Fe-NC maintained a meso‑macroporous structure with a large specific surface area of 1381 m2/g and superior electrochemical properties. Its calculated specific capacitance and electron transfer resistance were 5.7 and 0.4 times of the carbon felt (CF) group. The bacterial and archaeal gene loads of Fe-NC biofilm after multiple acclimation cycles were 5.69E+10 and 1.86E+9 copies/cm2 and Proteiniphilum and Methanobacterium were the most enriched syntrophs from stage Ⅰ to stage Ⅱ acclimation. Corresponding maximum methane yield and content achieved were 0.31 m3 CH4/kg COD and 92.8 %, and its CO2-dependent methane production was improved by 107.6 %. Mechanistic investigations showed that Fe-NC biofilm improved enzyme-associated CO2 reduction pathway companying by promoting the intra- and extracellular electron transfer as well as ATP synthesis, therefore favoring methanogenic energetic metabolism. More importantly, an enhanced proton-coupled electron transfer (PCET) process was proposed within Fe-NC biofilm, providing a synergistic advantage over unbalanced conventional sole electron/proton transfer. This work provides an effective strategy to strengthen the waste-to-energy and biogas upgrading technology, potentially bringing economic benefits to wastewater treatment.